A user's guide to capitalism and schizophrenia: Deviations from Deleuze and Guattari - Massumi, Brian (Cambridge, Massachusetts MIT Press, 1992)
A User's Guide to Capitalism and Schizophrenia is a playful and emphatically practical elaboration of the major collaborative work of the French philosophers Gilles Deleuze and Felix Guattari. When read along with its rigorous textual notes, the book also becomes the richest scholarly treatment of Deleuze's entire philosophical oeuvre available in any language. Finally, the dozens of explicit examples that Brian Massumi furnishes from contemporary artistic, scientific, and popular urban culture make the book an important, perhaps even central text within current debates on postmodern culture and politics.Capitalism and Schizophrenia is the general title for two books published a decade apart. The first, Anti-Oedipus, was a reaction to the events of May/June 1968; it is a critique of "state-happy" Marxism and "school-building" strains of psychoanalysis. The second, A Thousand Plateaus, is an attempt at a positive statement of the sort of nomad philosophy Deleuze and Guattari propose as an alternative to state philosophy.Brian Massumi is Professor of Comparative Literature at McGill University.A User's Guide to Capitalism and Schizophrenia is a playful and emphatically practical elaboration of the major collaborative work of the French philosophers Gilles Deleuze and Felix Guattari. When read along with its rigorous textual notes, the book also becomes the richest scholarly treatment of Deleuze's entire philosophical oeuvre available in any language. Finally, the dozens of explicit examples that Brian Massumi furnishes from contemporary artistic, scientific, and popular urban culture make the book an important, perhaps even central text within current debates on postmodern culture and politics.Capitalism and Schizophrenia is the general title for two books published a decade apart. The first, Anti-Oedipus, was a reaction to the events of May/June 1968; it is a critique of "state-happy" Marxism and "school-building" strains of psychoanalysis. The second, A Thousand Plateaus, is an attempt at a positive statement of the sort of nomad philosophy Deleuze and Guattari propose as an alternative to state philosophy.Brian Massumi is Professor of Comparative Literature at McGill University.